Free standing nanoindentation of penta-graphene via molecular dynamics: Mechanics and deformation mechanisms. (May 2023) - Han, Tongwei; Li, Ren; Zhang, Xiaoyan; Scarpa, Fabrizio
Abstract: The deformation and fracture mechanisms of penta-graphene under different loading conditions are still unclear and not thoroughly investigated. Hereby, the mechanical and transition/failure deformation properties of penta-graphene are investigated by using free standing nanoindentation techniques simulated via molecular dynamics. The indentation behaviors of penta-graphene under spherical and cylindrical indenters are compared and analyzed parametrically by considering the effects of the spherical/cylindrical indenter size, the loading rate and temperature. The results show that penta-graphene under spherical and cylindrical indentation exhibits unusual plastic deformation characteristics, which are consistent with those previously observed under uniaxial tensile and shear loading. The plastic deformation is originated from the pentagon-to-polygon structural transformation occurring at large indentation depths. The force at failure of the penta-graphene under spherical indenter is significantly lower than the one observed under cylindrical indenter; this is due to the small interaction area and high stress concentration caused by spherical indenter. We also identify the indentation parameters to accurately predict the mechanical parameters of penta-graphene using spherical or cylindrical indenters, and how these parameters influence the nanoindentation results. It is found that under both spherical and cylindrical indenter the Young's modulus of the penta-graphene is not sensitive to the loading rate, but generally decreases with the increasing temperature. Graphical abstract: Image 1 Highlights: The mechanics of PG under different indenters are examined using nanoindentation. PG under indentation loading exhibits unusual plastic deformation characteristics. The mechanism of plastic deformation is originated from structural transformation. The indentation parameters to predict the mechanical parameters are identified.